Studies the physico-chemical characteristics of guava (Psidium guajava) fruits in Chittorgarh district of Rajasthan (Indian Journal of Arid Horticulture, 2010)
The nutritional survey was conducted on guava fruit orchards at different locations in Chittorgarh district of Rajasthan. Variation in different characteristics of fruits was observed. The fruit weight is varied from 167.51 to 185.64g. The pooled average polar fruit diameter and equatorial fruit diameter varied from 5.58 to 6.01 cm and 6.03 to 6.51 cm, respectively. The seed weight varied from 3.53 to 5.11g, pulp to stone ratio from 87.83 to 115.67g, fruit yield per tree from 50.73 to 69.83 kg plant' were recorded. The total soluble solids content varied from 10.76 to 11.78° Brix, total acidity from 1.85 to 1.93 per cent, ascorbic acid content from 411.65 to 581.50 mg/100g pulp, total sugar from 1.71 to 2.10 per cent, reducing sugar from 4.97 to 6.28 per cent and TSS/acidity ratio from5.58 to 6.35 recorded.
Keywords: Guava; physico-chemical characteristics; nutrition, yield.